Síntese e atividade de compostos potencialmente larvicidas frente ao Aedes aegypti - Santos, Sandra Regina Lima (2014)
Nowadays, themost importantarboviral diseaseaffecting humans is dengue.The Dengue constitutesa serious problem of public health in the world; its managementis basically restrictedto the controlling of themain vector, Aedes aegypti. In absence of an effective and safe prevention vaccine for this disease, the main preventive measureavailablefor infections causedby dengue virusisvector controlthrough the use of chemicalinsecticides andlarvicides. This strategy, however, hasshownselectivity inmaintenanceofresistant mosquitopopulations against insecticidesconventionallyused. In this context, the development of new technologies and alternative strategies to combat Aedes aegypti is essential to reduce the disease incidence.Thus, theobjective of this studywas to evaluatethe activity of new compoundsagainst larvaeof Aedesaegyptiand it was addressed two aspects:the evaluationof terpenesand derivatives, as well as the synthesis ofcompoundswith the potentialto acttowardsofmetabolism oftryptophan. Initially were selected 21 commercially compounds available, subdivided into two groups: 10 aromatic and 11 aliphatic bicyclic. Bioassays were performed using 20 larvae per test in cups containing 20 ml of an aqueous solution containing varying concentrations of test compounds in triplicate. Among the aromatic compounds the p-cymene demons the best potency LC50 = 51 ppm and the Resorcinol exhibited the lower potency LC50 = 577 ppm. Within the aliphatic group the ( )-camphene showed the best activity LC50 = 220 ppm and 1,8-cineole exhibited lower potency LC50 = 1419 ppm. It was Identified that the structural characteristics of the derivatives of essential oils may contribute to the understanding the larvicidal activity of these compounds. In this sense, we report the importance of the lipophilic groups presence increasing the potency of these substances as well as reducing the potential larvicide in derivatives held hydroxyl in the molecule. Subsequently, twelve compoundskynureninederivativesweresynthesized according tovariousmethods, followed bythe identificationby thin layer chromatography and melting point, purified by silica gel 60 column chromatography and characterized by 13C and1H NMR , MS and IR. Allsynthetic intermediateswere evaluated forlarvicidal activityandobserved thatcompounds 2-amino-a-chloroacetophenone replacedtested proved tobepotent larvicides agentsagainstAe. aegypti, with LC50valuesranged from4.29 to 11.71ppm. However, thecompounds 2-acetylamino-2-[2 - (2-amino-fenilas-substituted)-2-oxoetila] malonic aciddiethylester andkynurenine derivatives, showed nosignificant activity againstl arvae of the Ae.aegypti.